The boy who loved words - Schotter, Roni.; Potter, Giselle (New York : Schwartz & Wade Books, 2006)
Selig, who loves words and copies them on pieces of paper that he carries with him, goes on a trip to discover his purpose.
Publisher's Weekly
Booklist
Kirkus Starred
2.9
K-3
Keywords: Language and languages -- Juvenile fiction; Vocabulary -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Language and languages -- Fiction; Vocabulary -- Fiction; Self-actualization (Psychology) -- Fiction; Language and languages -- Fiction; Vocabulary -- Fiction; Self-realization -- Fiction